Cytokine preconditioning of engineered cartilage provides protection against interleukin-1 insult. Issue 1 (December 2015) - Tan, Andrea; VandenBerg, Curtis; Attur, Mukundan; Abramson, Steven; Knight, Martin; Bulinski, J.; Ateshian, Gerard; Cook, James; Hung, Clark
Abstract Background During osteoarthritis and following surgical procedures, the environment of the knee is rich in proinflammatory cytokines such as IL-1. Introduction of tissue-engineered cartilage constructs to a chemically harsh milieu may limit the functionality of the implanted tissue over long periods. A chemical preconditioning scheme (application of low doses of IL-1) was tested as a method to prepare developing engineered tissue to withstand exposure to a higher concentration of the cytokine, known to elicit proteolysis as well as rapid degeneration of cartilage. Methods Using an established juvenile bovine model system, engineered cartilage was preconditioned with low doses of IL-1α (0.1 ng/mL, 0.5 ng/mL, and 1.0 ng/mL) for 7 days before exposure to an insult dose (10 ng/mL). The time frame over which this protection is afforded was investigated by altering the amount of time between preconditioning and insult as well as the time following insult. To explore a potential mechanism for this protection, one set of constructs was preconditioned with CoCl2, a chemical inducer of hypoxia, before exposure to the IL-1α insult. Finally, we examined the translation of this preconditioning method to extend to clinically relevant adult, passaged chondrocytes from a preclinical canine model. Results Low doses of IL-1α (0.1 ng/mL and 0.5 ng/mL) protected against subsequent catabolic degradation by cytokine insult, preserving mechanical stiffness and biochemical composition. Regardless of amount of time between preconditioning scheme and insult, protection was afforded. In a similar manner, preconditioning with CoCl2 similarly allowed for mediation of catabolic damage by IL-1α. The effects of preconditioning on clinically relevant adult, passaged chondrocytes from a preclinical canine model followed the same trends with low-dose IL-1β offering variable protection against insult. Conclusions Chemical preconditioning schemes have the ability to protect engineered cartilage constructs from IL-1-induced catabolic degradation, offering potential modalities for therapeutic treatments.